Noble metal nanoparticles and nanodiamond modified strontium titanate photocatalysts for room temperature CO production from direct hydrogenation of CO2 - Mohit Yadav; Tamás Gyulavári; Janos Kiss; Kornélia B. Ábrahámné; Anastasiia Efremova; Ákos Szamosvölgyi; Zsolt Pap; András Sápi; Ákos Kukovecz; Zoltán Kónya (Journal of CO2 Utilization, 2023)
The activation and conversion of CO2 can be achieved on multifunctional catalytic sites at the metal/oxide interface by taking advantage of the synergy between noble metal nanoparticles and supports. Herein, sequential deposition of noble metals (Ru, Rh, and Pt) and nanodiamonds (NDs) was carried out on the surface of strontium titanates (STO). The noble metals and NDs were deposited in either 1 wt% or 10 wt%. The samples were characterized with in-situ as well as ex-situ spectroscopic and microscopic techniques and tested towards photocatalytic CO2 hydrogenation. The sequential deposition of the noble metals and NDs enhanced light absorption properties, which also led to higher photocatalytic activity. The STO-ND-Ru sample had the highest photocatalytic CO2 hydrogenation efficiency (47.5%) and showed improved selectivity for CH4 (14.5%). Diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) studies showed that the hydrogenation of CO2 to CO and CH4 followed different mechanisms for pristine STO and STO-ND-Ru.